Il pubblico del festival Torinodanza (2018): Teorie, rilevamento e prospettive di ricerca - Giannasca, Emanuele (Mimesis Journal, 2019)
Aiming at encouraging audience engagement and development, surveys are a necessary tool in order to understand social, cultural, and economic phenomena that inform the way people experience live performances. This essay aims to analyse data from audience surveys carried out during Torinodanza Festival 2018. This study presents an outline of the spectators’ socio-demographic profile and an analysis of data related to the audience’s emotional and cognitive experience, showing the level of engagement towards the Festival programme.